HOW TO IMPROVE ENGLISH SPEAKING SKILLS (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
This article discusses speaking in a foreign language, whether it belongs to a certain circle or the most useful aspects. Basic technique, classical approach to language learning, lingo-cultural approach, communicative approach, intensive technique, emotional and meaningful test preparation method. You can mix and match integrated methods.